Tourism Gentrification in Bali, Indonesia: A Wake-up Call for Overtourism - Suyadnya, I Wayan (Masyarakat: Jurnal Sosiologi, 2021)
Many tourists destinations experience revitalisation through funding from foreign capital that is brought by gentrification. As a result, tourist areas transform into regions that are friendly toward tourists and investment. Various studies see gentrification as an expression of consumer demand, individual preferences over the law of supply and demand. However, this article argues that tourism gentrification shows a different dynamic, namely driving the significance of tourism growth that supports overtourism. This article focuses on the reason why Balinese do not feel that the phenomenon of gentrification and the development of protests are a part of the symptom of overtourism. Research was conducted in the three tourist areas of Sanur, Kuta, and Ubud. These locations were indicated as gentrification areas. The three locations present a fascinating tension regarding the role of tourism to draw the expansion of capitalism through capital investment and corporate actions, as well as opposed interests that struggle to control the production, representation, and image of tourism in Bali. Research results indicated that the gentrification of tourism not only causes land and property rental values to increase, but also drives land transformation and utilization in Bali. The gentrification of tourism in Bali refers to the socio-spatial transformation by which private corporations and the state invest in low-class areas, marked by the construction of tourist facilities that encourage signs of overtourism.